Dynamic channel allocation strategy for quality of service enhancement in wireless ad hoc networks. (2nd February 2022) - Wu, Chenyang; Ji, Xiaopeng; Dai, Yuewei
Abstract: The quality of service (QoS) is a momentous performance index of wireless ad hoc networks. However, unreasonable channel allocation will degrade the QoS. During the process of channel allocation, if user requests for idle channels are rejected, the QoS will lower accordingly. In this paper, we propose a dynamic channel allocation strategy for QoS enhancement to enhance the QoS and reduce the rejection rate of idle channel requests. First of all, the channel availability model is modeled as a Continuous Time Markov Chain in a bid to calculate the channel availability which is used to compute the channel availability factor (CAF) and the channel availability threshold (CAT). Then, the dynamic channel allocation process is achieved based on the comparison result of CAF and CAT. Ultimately, the QoS is guaranteed by exploiting the earliest deadline first algorithm to forward packets and enhanced by using the packet segmentation algorithm to divide packets into packet flows. The simulation results prove that the proposed channel allocation strategy increases the packet delivery ratio and throughput, decreases the end‐to‐end delay and total overhead and shows a QoS enhancement than existing schemes.